KETERLIBATAN WARGA LINGKUNGAN DALAM KEGIATAN PEWARTAAN DI STASI YOHANES GABRIEL PERBOYRE - Pandi, Ali; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2020)
The purpose of the study is to identify the involvement of the members of Basic Christian Community in the proclamation of the good news. The research was conducted at Yohanes Gabriel Perboyre Christian Ecclesial Community, Surabaya. The research was conducted using a descriptive qualitative method. The informants selected for the study consisted of Basic Chistian Community heads, Christian Ecclesial Community heads, and the Catholic faithful. Data collection was done by using personal interview techniques. The results of the study indicated that the spirit or enthusiasm of the members of Basic Christian Communities was still low. This can be proven by the small number of the Catholic faithful who regularly involved in each activity related to the proclamation of the good news. The result of the research also found out that there were two major inhibiting factors for the involvement in the proclamation of the good news which were the business of the work and the difficulties of organizing the time for attending the good news proclamation activities.